Spatial sputtering of fused silica after a laser-induced exploding caused by a 355 nm nd: YAG laser - Peng, Ge; Zhang, Peng; Dong, Zhe; Chen, Jiaxuan; Liang, Lingxi; Zhu, Chengyu; Gao, Qiang; Lu, Lihua (Frontiers in Physics, 2022)
To alleviate laser-induced threats in the high-power laser systems, it is necessary to understand the debris propagation process and distribution characteristics, then take protection and cleaning strategies to sustain an ultra-clean environment. This work presents an experimental investigation of the sputtering behaviors of the laser-induced fused silica debris to clarify their longitudinal propagation and bottom distribution on the millimeter scale. Two types of polished surfaces with more than three orders of magnitude differences in surface roughness were adopted. The result reveals the centralized/decentralized distribution and the ability of long-range movement of debris propelled by the melting and mechanical failure. The maximum largest dispersion angle (LDA) appears at 18J/cm2 for debris within 10–20 μm from the Two Sides polished surface; debris <30 μm dominate the major quantity in the longitudinal propagation, and their centralization ability profoundly relies on the laser fluence and the surface roughness of the target; the diameter of the debris with long-range movement generally below 20 μm. This study could guide for establishing the overall dynamic cleaning strategy inside the high-power laser systems.